Pencabutan Hak Politik Pada Tindak Pidana Korupsi: Apakah Perlu - Al Fanany Farcham, Muhammad Faqih; Permatasari, Putri Intan (Eastasouth Institute, 2024)
Corruption is a very detrimental crime, having a broad negative impact on the social, economic and political aspects of the country. In dealing with this problem, Indonesia has implemented preventive and repressive efforts, but many public officials are still involved in corruption. One of the proposed sanctions is the revocation of political rights for perpetrators of criminal acts of corruption. This research evaluates the urgency and effectiveness of revocation of political rights as an additional punishment, and considers a human rights perspective. Using normative juridical methods, this research analyzes written law and relevant doctrine, as well as examining primary and secondary legal materials. The research results show that revoking political rights can have a deterrent effect and prevent the repetition of criminal acts of corruption, but clearer regulations regarding time limits and implementation are needed so as not to violate human rights. It is hoped that this research can provide recommendations for policy makers and law enforcers in improving the legal system to ensure fair and effective law enforcement in eradicating corruption.